Prospective evaluation of blood pressure, heart rate, and side effects in hypertensive patients using low-dose oral minoxidil for hair loss - Müller Ramos, Paulo [UNESP] (2024)
Dermatology Department Universidade Estadual Paulista - UNESP, São Paulo